PWE-254 Impact of induction dosing on maintenance outcome with adalimumab in Crohn's disease. (28th May 2012) - Colombel, J-F; Rutgeerts, P J; Sandborn, W J; Reinisch, W; Loftus, E V; Tang, J; Pollack, P F; Yang, M; Patel, S P; Huang, B; Chao, J; Mulani, P M
Abstract : Introduction: Two induction regimens of adalimumab are used in Crohn's disease (CD): 160/80 mg or 80/40 mg at Weeks 0/2. We compared long-term efficacy for patients who received 160/80 mg vs 80/40 mg as induction therapy followed by eow maintenance therapy. Methods: Data were from two randomised, double-blinded, placebo-controlled efficacy and safety trials in moderate to severe CD. EXTEND, a 52-week study in patients with mucosal ulceration, used the 160-/80-mg induction regimen. CHARM, a 56-week study for maintenance of clinical remission, used the 80-/40-mg induction regimen. All patients who started with induction dose and were randomised to eow plus dropouts prior to Week-4 randomisation were included. Missing Crohn's Disease Activity Index (CDAI) scores were imputed with both non-responder imputation (NRI) and last observation carried forward (LOCF). Remission (CDAI <150) and hospitalisation were compared between induction regimens. To incorporate the correlation between visits for a patient, a logistic regression with the patient-level random intercept using all the time points after Week 4 was constructed to compare likelihood of remission, controlling for baseline CDAI, fistula, prior use of an anti–tumour necrosis factor therapy, concomitant medications, CD duration, and other factors. Results: 70 patients in the 160-/80-mg group were compared with 336 patients in the 80-/40-mg group. Baseline characteristics were similar except for greater rates of rectal/anal CD in the 160-/80-mg group and greater use of concomitant steroids in the 80-/40-mg group. Compared with the 80-/40-mg group, the 160-/80-mg group had a greater percentage of time in remission from Week 0–52 (36% vs 25%; p<0.05, NRI), significantly fewer hospitalisations per patient (0.09 vs 0.23; p<0.05), and significantly fewer CD-related hospitalisations (0.07 vs 0.18; p<0.05). Patients in the 160-/80-mg group were significantly more likely to be in remission during Weeks 4 to 52 than were patients in the 80-/40-mg group after adjusting for baseline characteristics (adjusted OR 4.8; p<0.001). LOCF results for remission analysis were consistently similar. The 160-/80-mg regimen did not appear to lead to a higher rate of AEs. Conclusion: The 160-/80-mg induction regimen of adalimumab was associated with a greater likelihood of remission, more time in remission, and fewer hospitalisations during eow maintenance therapy compared with the 80-/40-mg regimen. Competing interests: J-F Colombel Consultant for: Abbott, Speaker bureau with: Abbott, P Rutgeerts Grant/Research Support from: Abbott, Consultant for: Abbott, Speaker bureau with: Abbott, Conflict with: Abbott, W Sandborn Grant/Research Support from: Abbott, Consultant for: Abbott (fees paid to Mayo), W Reinisch Consultant for: Abbott, Conflict with: Abbott, E Loftus Jr Grant/Research Support from: Abbott, Consultant for: Abbott, J Tang Consultant for: Abbott, Employee of: Analysis Group, P Pollack Shareholder with: Abbott, Employee of: Abbott, M Yang Shareholder with: Abbott, Employee of: Abbott, S Patel Shareholder with: Abbott, Employee of: Abbott, B Huang Shareholder with: Abbott, Employee of: Abbott, J Chao Shareholder with: Abbott, Employee of: Abbott, P Mulani Shareholder with: Abbott, Employee of: Abbott.